2012
DOI: 10.1097/wnr.0b013e32835542b0
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Alzheimer’s disease inflammatory signaling through soluble micro-RNA

Abstract: Alzheimer’s disease is a progressive, neurodegenerative disorder that develops within the limbic system, spreading radially into anatomically linked brain association areas as the disease progresses. Analysis of temporal-lobe association of neocortex-derived extracellular fluid and cerebrospinal fluid from Alzheimer’s disease patients shows an abundant presence of micro-RNA (miRNA), including the proinflammatory miRNA-146a and miRNA-155. Using a novel and highly sensitive LED-Northern dot-blot focusing techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 24 publications
(85 reference statements)
4
89
0
Order By: Relevance
“…After miRNAs were first found in CSF [28], several more studies have demonstrated the presence of miRNAs in CSF and their potentials as biomarkers for neurological disease [32][33][34][35]. Further, a study comparing miRNA expression profile from serum and CSF has revealed that miRNA expression pattern is quite consistent among different subjects when miRNAs are from the same type of bio-fluid (serum or CSF).…”
Section: Journal Of Pharmacogenomics and Pharmacoproteomicsmentioning
confidence: 99%
“…After miRNAs were first found in CSF [28], several more studies have demonstrated the presence of miRNAs in CSF and their potentials as biomarkers for neurological disease [32][33][34][35]. Further, a study comparing miRNA expression profile from serum and CSF has revealed that miRNA expression pattern is quite consistent among different subjects when miRNAs are from the same type of bio-fluid (serum or CSF).…”
Section: Journal Of Pharmacogenomics and Pharmacoproteomicsmentioning
confidence: 99%
“…Age-matched control and 5xFAD brain and/or retina at 0, 1.5, 3 and 5 months were analyzed for Aβ40 and Aβ42 peptide and COX-2 and CRP protein levels using ELISA and Western analysis [3,[5][6][7][8]. Further details on the quality control for these 5xFAD brain and retinal samples, sample handling and analysis have been recently published [3,[18][19][20][21].…”
Section: Reagents Brain and Retinal Tissues Protein Extraction And mentioning
confidence: 99%
“…Out of multiple Tg-AD models studied by our laboratory (Tg2576, PSAPP, 3xTg-AD, etc.,) the 5xFAD model exhibits the most rapid and prolific accumulation of Aβ42 peptides in the brain and retina of any Tg-AD animal studied to date [2][3][4]. Whether amyloidogenesis originates independently in the brain and retina, or whether amyloidogenic signals originate in the brain and spread via the primary visual cortex and thalamus to the retina is open to question, but current data now favor the latter possibility [4][5][6][7][8]. Several laboratories have independently studied the effects of supplementing the diets of amyloidoverexpressing Tg-AD murine models (Tg-2576, APP/PS1, 5xFAD, etc.,) with aluminum (as chloride, lactate, maltolate or sulfate) and have evaluated the impact of ingested aluminum with pathological outcome [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Given that some human cancer cells secrete miRNAs into their extracellular environment and body fl uids, [24][25][26] it was hypothesized that MB cell lines may secrete miRNAs into their spent culture medium. To test this hypothesis, 3 cell lines representing MB subtypes D341 and D283 (metastasis-related group 3 and group 4 MB subtypes) [27] and DAOY (sonic hedgehog-related) were cultured individually for 72 h in vitro and miRNAs expression was analyzed in the lysates of each MB cell line and in their corresponding culture media.…”
Section: Detection Of Ex-mirnas In Cultured Medium Of Mb Cell Lines Bmentioning
confidence: 99%